The first record of Cavernulina orientalis (Thomson & Simpson, 1909) (Octocorallia: Pennatulacea: Veretillidae) from the Bay coast of Visakhapatnam, Andhra Pradesh - Veena, S.; Kaladharan, P. (Zootaxa, 2012)
Benthic fauna from in and around Visakhapatnam has been studied by: Radhakrishna (1964); Sudarsan (1983); Adiseshasai (1992) and Vijayakumaran (2003). Previous records have mentioned the collection of specimens of the sea pen genus Cavernularia Valenciennes, 1850 from these waters (Radhakrishna 1964) but species of the closely related (or perhaps synonymous) genus Cavernulina Kuekenthal & Broch, 1911 have not been identified until now.